In Situ Mucoadhesive Nasal Gel: A Novel Approach for Enhanced Drug Delivery - Vivek Kashinath Baviskar; Yogesh P. Sharma; Dr. Sunil. K. Mahajan (Asian Journal of Pharmaceutical Research and Development, 2026)
In situ mucoadhesive nasal gels have emerged as a novel and effective approach for enhancing drug delivery through the nasal route, offering significant advantages over conventional dosage forms such as drops and sprays. The nasal cavity provides a highly vascularized surface, rapid onset of action, and avoidance of first-pass metabolism, making it an attractive pathway for both local and systemic drug delivery. However, rapid mucociliary clearance and limited residence time restrict the efficiency of traditional formulations. In situ gel systems address these limitations by undergoing a sol-to-gel transition upon exposure to physiological conditions such as temperature, pH, or ionic strength, forming a viscous gel that remains in contact with the nasal mucosa. The addition of mucoadhesive polymers further enhances retention by promoting strong interactions with mucin, thereby prolonging residence time and improving drug absorption. These systems utilize a combination of natural and synthetic polymers, along with suitable excipients, to achieve optimal gelation, stability, and controlled drug release. As a result, in situ mucoadhesive nasal gels offer improved bioavailability, sustained release, and reduced dosing frequency, leading to better patient compliance. They are particularly promising for the delivery of peptides, proteins, vaccines, and drugs targeting the central nervous system via the nose-to-brain pathway. Recent advancements, including nanoparticle-loaded gels and stimuli-responsive systems, have further expanded their therapeutic potential. Despite certain formulation and regulatory challenges, these systems represent a versatile and promising platform for advanced drug delivery applications.